2015
DOI: 10.1007/s00128-015-1588-3
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Contamination in an Indicator Fish Species from Andean Amazonian Rivers Affected by Petroleum Extraction

Abstract: Elevated mercury (Hg) concentrations in fish from Amazonia have been associated with gold-mining, hydroelectric dams and deforestation but few studies consider the role of petroleum extraction. Hg levels were determined in fish samples collected in three river basins in Ecuador and Peru with contrasting petroleum exploitation and land-use characteristics. The non-migratory, piscivorous species, Hoplias malabaricus, was used as a bioindicator. The rate of Hg increase with body weight for this species was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
1
10
0
1
Order By: Relevance
“…This type of disturbance usually generates inconveniences in the biological communities that inhabit the rivers and therefore can lead to the decrease of biodiversity and abundance. However, the case of oil or mining exploitation can be even more devastating because their impacts persist over time and are more complex and challenging to remove from the environment [10][11][12][13]64]. The impact of the latter type of stressors is very severe and interrupts the dynamics and ecological functions that normally are given by the site-specific conditions, the seasonal fluctuations of the physical-chemical variables, or the temporal patterns of rainfall, which determine the composition of aquatic invertebrate communities.…”
Section: Discussionmentioning
confidence: 99%
“…This type of disturbance usually generates inconveniences in the biological communities that inhabit the rivers and therefore can lead to the decrease of biodiversity and abundance. However, the case of oil or mining exploitation can be even more devastating because their impacts persist over time and are more complex and challenging to remove from the environment [10][11][12][13]64]. The impact of the latter type of stressors is very severe and interrupts the dynamics and ecological functions that normally are given by the site-specific conditions, the seasonal fluctuations of the physical-chemical variables, or the temporal patterns of rainfall, which determine the composition of aquatic invertebrate communities.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated U-Hg was also associated with increased fish consumption, which was higher in the Marañón ( ) than in other river basins. Elevated mercury in Amazonian fish has been associated with oil contamination, 5 and there is evidence that consumption of freshwater fish is associated with U-Hg concentrations. 6 However, previous studies from the same region, suggest that the main route of exposure to mercury in the area is through dermal uptake of mercury present in the water.…”
Section: Resultsmentioning
confidence: 99%
“…The Andean region and the Andean Amazon have been considered active mercury belts due to the constant volcanic and tectonic activity [59] . It has been reported that rivers drain Andean volcanic soils [99] , affecting the lower parts of the Amazonian river network with metals such as Hg [12] . In the Ecuadorian Amazon, a link between deforestation, soil erosion, and the leaching of naturally occurring Hg has been demonstrated [59] , additionally, in the Brazilian Amazon, erosion increased the superficial sediment mercury concentrations in the different aquatic systems [81] .…”
Section: Resultsmentioning
confidence: 99%